2012
DOI: 10.1021/bm201719s
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Control of Silk-Based Electrospinning

Abstract: Silk fibroin (SF) nanofibers, formed through electrospinning, have attractive utility in regenerative medicine due to the biocompatibility, mechanical properties and tailorable degradability. The mechanism of SF electrospun nanofiber formation was studied to gain new insight into the formation and control of nanofibers. SF electrospinning solutions with different nanostructures (nanospheres or nanofilaments) were prepared by controlling the drying process during the preparation of regenerated SF films. Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 126 publications
(133 citation statements)
references
References 30 publications
5
127
0
1
Order By: Relevance
“…All natural spider and silkworm silks appear to display a nanofibrillar substructure, and there is ample evidence that these fibrils contribute significantly to the prodigious mechanical properties of silks. 64,65 Assembly of RSF into fibrils with native-like structure has been demonstrated; 34,[38][39][40][41]43,44,54,57 however, while such fibrillar artificial silks are relatively robust compared to other biological materials and promise a novel range of properties in composite applications, 38,44 their mechanical properties still fall short of their natural silk counterparts. 9,38,40,43,44,54,57 The diminished capability of RSF to self-assemble is in line with past studies that have revealed deviations in the structure and bonding character of the RSF molecule.…”
Section: ■ Discussionmentioning
confidence: 99%
“…All natural spider and silkworm silks appear to display a nanofibrillar substructure, and there is ample evidence that these fibrils contribute significantly to the prodigious mechanical properties of silks. 64,65 Assembly of RSF into fibrils with native-like structure has been demonstrated; 34,[38][39][40][41]43,44,54,57 however, while such fibrillar artificial silks are relatively robust compared to other biological materials and promise a novel range of properties in composite applications, 38,44 their mechanical properties still fall short of their natural silk counterparts. 9,38,40,43,44,54,57 The diminished capability of RSF to self-assemble is in line with past studies that have revealed deviations in the structure and bonding character of the RSF molecule.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Recently, the electrospinning process has been developed to prepare SF-based biomaterials with a submicron diameter. In most of prior studies about the electrospinning of SF solution, the SF spinning dopes were also formed by using organic solvents [11][12][13][14], or further blending with poly (ethylene oxide), chitosan, collagen and other synthetic or nature polymers [15][16][17]. Only few researches were implemented using water as solvent and pure SF aqueous solution as spinning dope [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] The as-cast BSF and TSF lms are water soluble due to their random coil structure, post-treatment using organic solvents is required, such as methanol, ethanol. 18,19 To develop highly biocompatible silk broin material, using less toxic solvents is an important direction.…”
mentioning
confidence: 99%